Propuesta mejoramiento control interno al área de cartera de la copropiedad zona franca del pacifico. (2021)
Pacific Free Zone with morethan 25 years of experience located in the city of Palmira is a private industrial and logistics park with tax and customs benefits for industrial, logistics and commercial projects.